Peningkatan Kemampuan Analisis Fakta dan Opini Peserta Didik Kelas XI TEK 2 SMK Negeri 5 Surabaya dengan Model Pembelajaran Kooperatif - Aulia Fanny; Kaswadi Kaswadi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This study aims to describe the improvement of the ability to analyze facts and opinions in argumentation text of students of class XI TEK 2 SMK Negeri 5 Surabaya, as well as to describe the effectiveness of cooperative learning model in class XI TEK 2 SMK Negeri 5 Surabaya. This type of research is a class action research (PTK). This class action research was conducted in class XI TEK 2 of SMK Negeri 5 Surabaya in semester 1 of 2024/2025 academic year. The subjects of this study were students of class XI TEK 2 consisting of 31 students; 24 male students and 7 female students. Data collection techniques using direct observation and test methods. Based on the results and discussion, the following conclusions can be drawn. (1) There was an increase in the learning outcomes of students in class XI TEK 2 in learning to analyze facts and opinions in argumentation text. The increase in student learning outcomes was 37.5. In addition, the increase in learning outcomes did not only occur in students who had not met the minimum score in cycle I, but also in 4 groups at once. Even as many as three groups achieved maximum learning outcomes. (2) Cooperative learning model is effective in learning to analyze facts and opinions in argumentation text. The cooperative learning model encourages learners to actively discuss to determine facts and opinions in argumentation text in groups.